(untitled) (Clinics, 2022)
Objectives: The aim of this study was to conduct the translation and cross-cultural adaptation of the original Team Emergency Assessment Measure (TEAM) tool into the Brazilian Portuguese language and investigate the internal consistency, inter-rater reliability, and concurrent validity of this new version (bp-TEAM). Methods: Independent medical translators performed forward and backward translations of the TEAM tool between English and Portuguese, creating the bp-TEAM. The authors selected 23 videos from final-year medical students during in-situ emergency simulations. Three independent raters assessed all the videos using the bp-TEAM and provided a score for each of the 12 items of the tool. The authors assessed the internal consistency and the inter-rater reliability of the tool. Results: Raters assessed all 23 videos. Internal consistency was assessed among the 11 items of the bp-TEAM from one rater, yielding a Cronbach's alpha of 0.89. inter-item correlation analysis yielded a mean correlation coefficient rho of 0.46. Inter-rater reliability analysis among the three raters yielded an intraclass correlation coefficient of 0.86 (95% CI 0.83‒0.89), p < 0.001. Conclusion: The Brazilian Portuguese version of the TEAM tool presented acceptable psychometric properties, similar to the original English version.